DESAIN TUGAS BELAJAR BERBASIS PAMERAN DALAM PEMBELAJARAN DIMENSI TIGA JENJANG PENDIDIKAN MENENGAH - Rahelia Siahaan; Mohamad Rif’at; Sugiatno Sugiatno (Universitas Tanjungpura, 2019)
AbstractThis research intends to develop an exhibition-based learning task design in three-dimensional learning. The learning process uses a scientific approach to improve students' mathematical representation abilities. This reseach uses R&D methods with ADDIE models. The subjects of the research were students in SMA Negeri 1 Sekayam and SMA Negeri 2 Sekayam. The data collection instruments consisted of a validation questionnaire of the exhibition-based learning task design, observation sheets of student learning activities, and test of mathematical representation ability. The results showed that, (1) the exhibition-based learning task design in three-dimensional learning is valid and feasible to use. (2) The learning process occur effectively, based on results of the observation sheet analysis of student learning activities, which shows 7 out of 9 aspects of the activity has been